KESIAPAN SEKOLAH DI TINJAU DARI USIA DAN KECERDASAN DI SD MUHAMMADIYAH KABUPATEN ROKAN HULU RIAU - Irawan, Alucyana; Antony Putra, Ary; Hidayat, Bahril (UIR Press, 2021)
School readiness is essential for children because children ready to enter elementary school will benefit and progress further than those not prepared to enter elementary school. Kustimah (2008) stated that the factors that influence children's readiness to enter elementary school include age and level of intelligence. Age factors can affect thinking and work. A person's mindset and grasping power are also influenced by age. The older a person gets, the more his grasping ability and attitude will develop and, of course, affect the knowledge he gains. This study is a quantitative study that aims to determine the effect between age and intelligence of early childhood on their readiness to enter elementary school by using psychological test tools Nijmeegse Schoolbekwaamheids Test (NST) and Colored Progressive Matrices (CPM). Studies conducted this research at Muhammadiyah Elementary School, Rokan Hulu Regency, Riau Province. From 85 respondents, using the ordinal regression model, the results were 0.998, 0.998, 0.278, and 0.887; this shows that age and intelligence have no significant effect on children's readiness to enter school.